Evolution of the quality of employment in Costa Rica in the last decade - Villegas González, Braulio (2022)
This paper has the objective of analyzing the evolution of the quality of employment in the country in recent years and its incidence in different subpopulations, for which presents a measurement through a multidimensional approach, and this phenomenon is analyzed through the different aspects that comprise it, at the same time that a synthetic indicator is constructed to achieve a general measurement of the quality of employment. Despite the fact that between 2013 and 2015, the indicators showed a slight deterioration in the quality of employment, mainly those related to income and benefits from employment and working time and work-life balance, since 2011 the general indicator has remained relatively constant. When analyzing the quality of employment by subgroups of employed people, the precariousness of the situation is denoted for older adults, positions with medium and low qualifications, the self-employed and people employed in activities of households as employers, agriculture, construction, transportation and hotels and restaurants.